The Difference of Corporate Social Responsibility Disclosure and Implementation of Good Corporate Governance Based on Company Size - Richo Aviyanti; David Kaluge (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
This research aims to test and analyze the difference of CSR disclosure and the implementation of GCG based on company size namely large, medium, and small-scale companies. This research used a Multivariate Analysis of Variance (MANOVA) test with manufacturing companies listed on the Indonesia Stock Exchange in 2018 as many as 158 companies as the sample. The test shows that CSR disclosure in large-scale companies is different than the other. The large-scale companies reveal CSR more broadly than the medium and small-scale companies. Meanwhile, the medium and small-scale companies tend to have similarities of CSR disclosure (no different). In the implementation of GCG, there isn't a similarity in each size of those companies. Because of the differences, it makes that the implementation of GCG in large-scale companies better than medium-scale companies and small-scale companies.